Towards a Digital Desert Fireball Network for Meteorite Recovery - Towner, M.; Bland, Philip; Spurney, Pavel; Benedix, G.; Dyl, Kathryn; Bevan, A.; Vaughan, D. (Lunar and Planetary Science Institute, 2012)
We describe digital enhancements to the Desert Fireball Network, and detail the modelling and analysis work concerning the predicted fall rate over this next phase of the project.